“Existential Catastrophe Anxiety”: Phenomenology of Fearful Emotions in a Subset of Service Users With Severe Mental Health Conditions - Heggdal, Didrik; Borgejordet, Synne; Fosse, Roar (Frontiers in Psychology, 2022)
A subset of people with severe mental health conditions feels they are on the verge of losing control, even in the absence of external threats or triggers. Some go to extreme ends to avoid affective arousal and associated expectations of a possible, impending catastrophe. We have learned about such phenomenological, emotional challenges in a group of individuals with severe, composite mental health problems and psychosocial disabilities. These individuals have had long treatment histories in the mental health care system. They have been encountered at a specialized inpatient ward offering exposure-based therapy that aims at restoring self-regulation and recovery. We describe the phenomenology of anxiety and fear presented by these service users, a fear we have coined existential catastrophe anxiety (ECa). We also suggest a set of underlying, interacting, psychological mechanisms that may give rise to ECa, before comparing ECa with three other constructs previously described in the literature—annihilation anxiety, ontological insecurity, and affect phobia. These comparisons show several similarities, but also unique qualities with ECa and its suggested underlying mechanisms. The conceptualization of ECa may aid clinicians in addressing extreme experiential turmoil and engage service users in empowering therapeutic projects.